1997
DOI: 10.1007/s11664-997-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of GaBN ternary solutions by organometallic vapor phase epitaxy

Abstract: Layers of Gal_ BxN with compositions from x = 0 to x = 0.07 were grown by organometallic vapor phase epitaxy on sapphire substrates using trimethylgallium, triethylboron (TEB) and NH 3 as precursors. Growth was done in the temperature range from 450 to 1000~ The presence of boron was detected by the shift in the (0002) peak position in x-ray diffraction, by x-ray photoelectron spectroscopy, secondary ion mass spectrometry measurements, and by the changes in the band gap as measured by optical transmission. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…High boron containing layers growth by MOVPE has not been progressed a lot, which might be because the growth is normally performed at 1000 1C or above [2,4,10,11] in order to enhance B atoms diffusion, but at this high temperature the B-rich phase would poison the growth under high TEB/III ratio [12,13]. Low growth temperature can alleviate this problem and high boron incorporation can be achieved [13], but it does not facilitate growth of AlN for heterostructures or AlGaN MQWs.…”
Section: Introductionmentioning
confidence: 99%
“…High boron containing layers growth by MOVPE has not been progressed a lot, which might be because the growth is normally performed at 1000 1C or above [2,4,10,11] in order to enhance B atoms diffusion, but at this high temperature the B-rich phase would poison the growth under high TEB/III ratio [12,13]. Low growth temperature can alleviate this problem and high boron incorporation can be achieved [13], but it does not facilitate growth of AlN for heterostructures or AlGaN MQWs.…”
Section: Introductionmentioning
confidence: 99%
“…A.Y. Polyakov et al reported that the highest solubility of boron in GaN was 1% at 1000 °C by MOVPE [1]. Vezin et al produced a single phase of B x Ga 1-x N with x up to 4.56% by MBE [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that at the typical growth temperature for B x Ga 1Àx N (about 1000 1C) the phase diagram contains regions of spinodal decomposition or phase separation in the interval of 0.028oxo0.995 [1,2]. The first experimental results reported by Polyakov et al [3] showed that the highest boron solubility in GaN grown at 1000 1C on sapphire was about 1%. Wei et al [4] reported single-phase BGaN alloy on AlN/SiC with the highest boron content of 1.5%.…”
Section: Introductionmentioning
confidence: 99%